Uroptychus atlanticus, a new species of squat lobster (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic Ocean - Baba, Keiji; Wicksten, Mary K. (Zootaxa, 2017)
A new species of squat lobster, Uroptychus atlanticus, is described on the basis of a female specimen taken at a depth of 713–841 m in the southeastern Gulf of Mexico. The new species is readily distinguished from all known species of the genus from the western Atlantic by the very spinose carapace and pereopods, and a transverse row of spines on each of the abdominal tergites 1 and 2.